Physiological synchrony in electrodermal activity predicts decreased vigilant attention induced by sleep deprivation - Stuldreher, Ivo V.; Maasland, Emma; Bottenheft, Charelle; van Erp, Jan B. F.; Brouwer, Anne-Marie (Frontiers in Neuroergonomics, 2023)
When multiple individuals are presented with narrative movie or audio clips, their electrodermal activity (EDA) and heart rate show significant similarities. Higher levels of such inter-subject physiological synchrony are related with higher levels of attention towards the narrative, as for instance expressed by more correctly answered questions about the narrative. We here investigate whether physiological synchrony in EDA and heart rate during watching of movie clips predicts performance on a subsequent vigilant attention task among participants exposed to a night of total sleep deprivation. We recorded EDA and heart rate of 54 participants during a night of total sleep deprivation. Every hour from 22:00 to 07:00 participants watched a 10-minute movie clip during which we computed inter-subject physiological synchrony. Afterwards, they answered questions about the movie and performed the psychomotor vigilance task (PVT) to capture attentional performance. We replicated findings that inter-subject correlations in EDA and heart rate predicted the number of correct answers on questions about the movie clips. Furthermore, we found that intersubject correlations in EDA, but not in heart rate, predicted PVT performance. Individuals' mean EDA and heart rate also predicted their PVT performance. For EDA, inter-subject correlations explained more variance of PVT performance than individuals' mean EDA. Together, these findings confirm the association between physiological synchrony and attention. Physiological synchrony in EDA does not only capture the attentional processing during the time that it is determined, but also proves valuable for capturing more general changes in the attentional state of monitored individuals.